STRATEGI KONTEKSTUAL GEOLISTRIK BERBASIS SENSOR ECSG DALAM MENINGKATKAN PEMAHAMAN KONSEP FISIKA SMA - Marbun, Juliaster; Sitorus, Parlindungan; Sitinjak, Erni Kusrini; Pardede, Juven (Charm Sains: Jurnal Pendidikan Fisika, 2025)
In the era of technology-based learning, innovation is required to connect physics concepts with real-world phenomena to enhance students’ deep and meaningful understanding. This study aims to examine the effectiveness of a contextual learning strategy based on geoelectric principles using the Electrical Conductivity Soil Geoelectric (ECSG) sensor to improve high school students’ understanding of resistivity and electrical conductivity concepts. The research employed a quasi-experimental method with a one-group pretest–posttest design involving 34 students of class XI Science at SMA Negeri 1 Pagaran, North Tapanuli Regency. The research instruments consisted of a conceptual understanding test, procedural skills observation, and a student response questionnaire. The results showed an increase in the average score from 46.50 to 75.80 with an N-Gain value of 0.55, categorized as moderate. Procedural skills achieved an average score of 3.33 (good category), while student responses to the learning implementation reached an agreement level above 85% (very good category). These findings indicate that the application of geoelectric sensor technology in physics learning can enhance measurement accuracy, active participation, and students’ learning motivation. Thus, the ECSG-based geoelectric contextual approach is effective in strengthening conceptual understanding, scientific skills, and the relevance of physics learning to real-life contexts in agrarian environments.